The Effect of Organizational Culture on Employee Performance with Job Satisfaction as an Intervening Variable on Indonesian Maritime Transportation Company - Setyono, Langgeng; Larrantukal, Elang Gibran; Aulia, Mufida (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2024)
Having qualified human resources is one important factor in a business's success. Companies need to manage their human resources effectively and efficiently for employees to perform at their best. Authoritative culture and occupation fulfillment are a few factors that can further develop worker execution. As a result, this study is crucial for determining the impact of organizational culture on employee job satisfaction and performance. This study employs an explanatory and quantitative methodology. This study included 135 respondents, with the number of subjects calculated using the Slovin formula and selected through simple random sampling. SmartPLS 4.0 is used to process the PLS-SEM used in the data analysis method. The direct effect reveals that organizational culture significantly influences employee performance, job satisfaction significantly affects organizational culture, job satisfaction does not notably influence employee performance, and it does not act as a mediator in the relationship between organizational culture and employee performance. Maritime Transportation Company can use these findings to improve employee performance by emphasizing job satisfaction and fostering a supportive organizational culture.